Exome-wide analysis of rare coding variation identifies novel associations with COPD and airflow limitation in MOCS3, IFIT3 and SERPINA12. Issue 6 (25th February 2016) - Jackson, Victoria E; Ntalla, Ioanna; Sayers, Ian; Morris, Richard; Whincup, Peter; Casas, Juan-Pablo; Amuzu, Antoinette; Choi, Minkyoung; Dale, Caroline; Kumari, Meena; Engmann, Jorgen; Kalsheker, Noor; et al.
Abstract : Background: Several regions of the genome have shown to be associated with COPD in genome-wide association studies of common variants. Objective: To determine rare and potentially functional single nucleotide polymorphisms (SNPs) associated with the risk of COPD and severity of airflow limitation. Methods: 3226 current or former smokers of European ancestry with lung function measures indicative of Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2 COPD or worse were genotyped using an exome array. An analysis of risk of COPD was carried out using ever smoking controls (n=4784). Associations with %predicted FEV1 were tested in cases. We followed-up signals of interest (p<10 −5 ) in independent samples from a subset of the UK Biobank population and also undertook a more powerful discovery study by meta-analysing the exome array data and UK Biobank data for variants represented on both arrays. Results: Among the associated variants were two in regions previously unreported for COPD; a low frequency non-synonymous SNP in MOCS3 (rs7269297, pdiscovery =3.08×10 −6, preplication =0.019) and a rare SNP in IFIT3, which emerged in the meta-analysis (rs140549288, pmeta =8.56×10 −6 ). In the meta-analysis of % predicted FEV1 in cases, the strongest association was shown for a splice variant in a previously unreported region, SERPINA12 (rs140198372, pmeta =5.72×10 −6 ). We also confirmed previously reported associations with COPD risk at MMP12, HHIP, GPR126 and CHRNA5 . No associations in novel regions reached a stringent exome-wide significance threshold (p<3.7×10 −7 ). Conclusions: This study identified several associations with the risk of COPD and severity of airflow limitation, including novel regions MOCS3, IFIT3 and SERPINA12, which warrant further study.